-4(5y-7)-y=-2(y-5)

Simple and best practice solution for -4(5y-7)-y=-2(y-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(5y-7)-y=-2(y-5) equation:


Simplifying
-4(5y + -7) + -1y = -2(y + -5)

Reorder the terms:
-4(-7 + 5y) + -1y = -2(y + -5)
(-7 * -4 + 5y * -4) + -1y = -2(y + -5)
(28 + -20y) + -1y = -2(y + -5)

Combine like terms: -20y + -1y = -21y
28 + -21y = -2(y + -5)

Reorder the terms:
28 + -21y = -2(-5 + y)
28 + -21y = (-5 * -2 + y * -2)
28 + -21y = (10 + -2y)

Solving
28 + -21y = 10 + -2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2y' to each side of the equation.
28 + -21y + 2y = 10 + -2y + 2y

Combine like terms: -21y + 2y = -19y
28 + -19y = 10 + -2y + 2y

Combine like terms: -2y + 2y = 0
28 + -19y = 10 + 0
28 + -19y = 10

Add '-28' to each side of the equation.
28 + -28 + -19y = 10 + -28

Combine like terms: 28 + -28 = 0
0 + -19y = 10 + -28
-19y = 10 + -28

Combine like terms: 10 + -28 = -18
-19y = -18

Divide each side by '-19'.
y = 0.9473684211

Simplifying
y = 0.9473684211

See similar equations:

| x*y=630 | | x(2x+3)=4 | | 3(x-8)=9x | | 3x+9-2x=13 | | 4x^4-20x^2+16=0 | | 26x+12=5(5x+4) | | 10-(2*-4)+3x=16 | | (5u+3)(5-u)=0 | | 3x+9-2x=14 | | 2x-6x+9=x-6+15 | | (7x^2+5x)/(x^2+1)-5x/(x^2-6) | | 5w+2.7=12 | | 9x^2+169=0 | | 3x+9x-4=3(4x+9) | | -8=-(-6x-3) | | .5x-4=0 | | 2y+2(y-6)=8y-6(y-10) | | 9(x-1)=-126 | | 7/36*x=5 | | 4(x-2)=2x-2 | | 52=p-41 | | -(8x-4)-(3x-5)+10=-9(x-1)-(5x+8+3) | | 7x-2+5=10x+4 | | p+13=-10 | | 6x+9-5x=16 | | -2(3x-6)+5=-1 | | 8y=5y+9 | | Rx+Sy=Tfory | | (-5+7i)+(-8-9i)=0 | | (x)=3x+4 | | x-9/5-1=x-3/4 | | 5x-11=4x+6 |

Equations solver categories